2016
DOI: 10.1002/jbmr.3008
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Single Gene Polymorphisms and Bone Biomarkers and Response to Calcium and Vitamin D Supplementation in Young Adults Undergoing Military Training

Abstract: Initial military training (IMT) is associated with increased stress fracture risk. In prior studies, supplemental calcium (Ca) and vitamin D provided daily throughout IMT reduced stress fracture incidence, suppressed parathyroid hormone (PTH), and improved measures of bone health compared with placebo. Data were analyzed from a randomized, double-blind, placebo-controlled trial to determine whether single-nucleotide polymorphisms (SNPs) in Ca and vitamin D-related genes were associated with circulating biomark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 48 publications
3
19
0
2
Order By: Relevance
“…Hughes et al [15] recently observed an increase in trabecular vBMD (2%) and reduction in cortical vBMD (−0.3%) at the tibial metaphysis for women undergoing basic military training. An increase in trabecular vBMD is recognised as an early adaptation to mechanical loading [15,[36][37][38][39], whereas a reduction in cortical vBMD could be due to the unmineralised nature of new bone [10,15]. Basic military training is characterised by large increases in physical [40][41][42] and locomotor activity [40,43], and therefore the mechanical loading for the tibia is considered to be high [15,38,44,45].…”
Section: Tibial Volumetric Bone Mineral Densitymentioning
confidence: 99%
“…Hughes et al [15] recently observed an increase in trabecular vBMD (2%) and reduction in cortical vBMD (−0.3%) at the tibial metaphysis for women undergoing basic military training. An increase in trabecular vBMD is recognised as an early adaptation to mechanical loading [15,[36][37][38][39], whereas a reduction in cortical vBMD could be due to the unmineralised nature of new bone [10,15]. Basic military training is characterised by large increases in physical [40][41][42] and locomotor activity [40,43], and therefore the mechanical loading for the tibia is considered to be high [15,38,44,45].…”
Section: Tibial Volumetric Bone Mineral Densitymentioning
confidence: 99%
“…Vitamin D deficiency is characterized by bone loss, increased risk of fractures, and bone mineralization defects, which may lead to bone-related diseases such as osteoporosis, osteopenia, and osteomalacia [1][2][3][4]. Moreover, genetic variants of vitamin D3-related genes are associated with abnormal bone turnover and metabolism of bone diseases [5][6][7][8]. Vitamin D3 supplements are essential treatments for the prevention of bone loss, which underlies the mechanisms for decreasing bone resorption by osteoclasts and increasing bone formation by osteoblasts [9].…”
Section: Introductionmentioning
confidence: 99%
“…The absence of a protective effect with a greater increase in vitamin D status between weeks 1 and 15 in f-containing genotypes may represent an inability to respond fully to increasing vitamin D concentrations due to a less efficient VDR. This is supported by evidence from US Army recruits undergoing initial military training who displayed lower concentrations of bone formation markers in response to training with f-containing genotypes [30]. Additionally, the f-containing genotypes are known to be associated with reduced transcription of VDR-responsive genes [26] and it may be that relatively more vitamin D is required to undertake the bone remodelling that training requires.…”
Section: Vitamin D Receptor Gene-environment Interactionmentioning
confidence: 88%
“…The single nucleotide polymorphism FokI produces structural differences in the VDR [25] with functional consequences: the f allele is associated with reduced transcription of VDR-responsive genes compared with FF individuals [26]. The impact of this functional difference has been widely studied in relation to bone mineral density and osteoporosis [27][28][29], and the f allele or ff genotype is associated with lower concentrations of bone formation markers in US Army recruits [30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation